"He's not fat, he just has asthma": a qualitative study exploring weight management in families living with pediatric asthma. (2nd September 2022) - Clarke, Rebecca; Heath, Gemma; Nagakumar, Prasad; Pattison, Helen; Farrow, Claire
Abstract: Objective Children and young people living with asthma have an increased risk of overweight/obesity, leading to increased severity of asthma symptoms. Weight management has been recommended to improve asthma symptoms, however, there is limited understanding of how this is experienced or how children and young people with asthma and their families wish to be supported. The aim of this study was to explore parents and children/young people's views and experiences of managing weight while living with asthma, and to identify acceptable strategies for support.Methods: A qualitative methodological approach was taken to facilitate rich understanding of families' insights into weight management while living with asthma. In-depth interviews were conducted with nine families living with pediatric asthma ( n  = 9 parents, 9 young people). Data were analyzed using a Framework approach.Results: Findings indicated that family engagement with weight management behaviors was primarily influenced by perceptions of risk regarding asthma outcomes and beliefs about asthma control. Families also reported weight management engagement to be influenced by perceptions of the food environment, perceptions of the exercise environment (e.g. weather, anticipated social outcomes) and the availability of weight management support. Participants sought tailored support which gave consideration to the asthma-obesity interaction. It was suggested that this would help reduce perceptions of weight stigma in consultations, thereby supporting behavioral changes.Conclusions: Individualized weight management plans that consider families concerns about asthma-related risk are needed to manage weight in children and young people living with asthma.